THE USAGE OF THE VOLUNTARY CADAVER IN EDUCATION OF MEDICINE THROUGH SILENT MENTOR PROGRAM - Atmadja, Djaja Surya; Untoro, Evi (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2012)
In the medical education the usage of animals, cadavers or patients for medical training is common practice all over the world. It is widely accepted that the use of human body is better than animal.  The usage of cadavers for training in medical procedures and operations is more acceptable because it causes less harm than practicing directly to the patients. The cadavers for training are usually the unknown persons. Since the source of the unknown cadavers are decreasing from time to time, nowadays some Medical Faculties is looking for alternatives, such as the persons who voluntarily want to donate their bodies for medical education, known as Silent Mentor Program. In this program the live donor candidate (Silent Mentor) writes a will, in which  the donor states that he/she want to donate the body for teaching anatomy, training on medical intervention and surgery, research, organ transplantation or even for museum preparation. This program introduces firstly in Hua Lien, Republic of China (Taiwan) and now has been widely accepted by the community. In Indonesia, Silent Mentor is a new concept. Faculty of Medicine University of Indonesia has begun to adopt this system by sending some lecturers to learn about the Program. An healthy Indonesian male, 60 years old, Moslem, is the first SM candidate in Indonesia. He has signed a will in the front of his lawyer. Now there are about 20 SM candidates, who stated that they want to join Silent Mentor Program, but now is still waiting for preparation the administrative as well as legal procedures. In Indonesia, application of SMP needs some modification, due to differences in the culture, religion, facility and regulation
Keywords: medical education; corpse; voluntary donor